Meet me tonight in Atlantic City : a memoir - Wong, Jane (Tin House, 2023)
"In the late 1980s on the Jersey shore, Jane Wong watches her mother shake ants from an MSG bin behind the family's Chinese restaurant. She is a hungry daughter frying crab rangoon for lunch, a child sneaking naps on bags of rice, a playful sister scheming to trap her brother in the freezer before he traps her first. Jane is part of a family staking their claim to the American dream, even as this dream crumbles. Beneath Atlantic City's promise lies her father's gambling addiction, an addiction that causes him to disappear for days and ultimately leads to the loss of the restaurant. In her debut memoir, Jane Wong tells a new story about Atlantic City, one that resists a single identity, a single story as she writes about making do with what you have--and what you don't. What does it mean, she asks, to be both tender and angry? What is strength without vulnerability--and humor? Filled with beauty found in unexpected places, Meet Me Tonight in Atlantic City is a resounding love song of the Asian American working class, a portrait of how we become who we are, and a story of lyric wisdom to hold and to share"--